THEORETICAL APPROACHES TO THE EXPRESSION OF COMMUNICATIVE-PRAGMATIC FEATURES OF IRONY (Scientific journal of the Fergana State University, 2025)
This article explores theoretical approaches to understanding the communicative-pragmatic properties of irony, focusing on its linguistic and contextual dimensions. Irony, as a multifaceted communicative tool, operates in the interaction between literal and implied meanings, often relying on common knowledge and cultural symbols to fully understand the situation in the perception of the stylistic device of irony. The pragmatic meanings of irony in context are analyzed in speech acts, revealing the reality between the speaker, the listener and the speech process.